The Making of Roman Metal Ink Pen Nibs - David Sim (EXARC Journal)
Roman ink pen nibs have been made from different materials such as bone, horn, reed, iron, and copper alloys. This article deals with experiments to reproduce Roman ink pen nibs made from copper alloy and iron.